Estilo(s), heterogeneidade e sentidos: um olhar dialógico para a obra de Mia Couto a partir de Mulheres de cinzas - Lérco, Camila Cesário (2023)
This thesis is conducted in the Text and Discourse Research Line in the oral and written modalities of the Postgraduate Studies Program in Portuguese at PUC-SP and has as its theme the understanding of Mia Couto's style under the Bakhtinian gaze. The hypothesis presented is that the writer has his own style with regard to narrators and characters, which has a dialogical feature, since the dynamics of the dialogic relations established between them propitiate the crossing of alterities. The writer formulates the instance of the author-creator, who will be responsible for the work, making choices in relation to it, such as choosing to enunciate himself through paratexts, which frame the narrative itself, advancing the reader in the direction it will take and being the link between fiction and reality by referring to the historical fact thematized in the trilogy or mentioning the supposed historical research carried out for its production; and elaborate two character narrators, from different social groups, worldviews, languages and different ways of narrating: Imani, a Mozambican woman, and Germano de Melo, a Portuguese army officer, who dialogue with other voices. We chose as corpus the work Mulheres de cinzas, volume 1 of the trilogy As areias do imperador (2015-2017) – which also includes Sombras da água (volume 2) and O bebedor de horizontes (volume 3) –, due to the interest of verifying it in recent Mia Couto’s publication (within the last decade) how he elaborates, from the dialogical relations established by the voices present in the text, the link already known in his production between fiction and history, bearing in mind that such publication seems to have a greater proximity to the reality/history. It is proposed to observe to what extent this treatment helps to think about his style. The research focused on the opening work of the collection, considering it by itself to be quite representative of the discursive dynamics verified in the trilogy. In Mulheres de cinzas, the heterogeneity of subjects in conflict in a given chronotope is already designed, established by the dialogism established between the voices of the novel. In this sense, the research is guided by the following question: What is Mia Couto's style that we understand from Mulheres de cinzas? To answer this question, our general objective is: to reflect, from the dialogical perspective of the discourses, on the way in which the writer's style is established, in view of the chosen concrete utterance. It seeks to note how the voices that appear in the novel dialogue and how and to what extent this interaction helps to think about his style. As specific objectives, we have: (1) to identify the voices of the novel and verifying the relationships they establish in it, considering heterodiscourse as a category of analysis; (2) to observe how and why the relationships that these voices establish contribute to understanding the Mozambican writer's style. From the methodological point of view, this research has a qualitative approach and a described and interpretative nature, since we will reproduce and analyze excerpts from the novel. The results confirm our hypothesis, by indicating that, in fact, the voices that give life to the analyzed novel dialogue because they establish meanings from the representation of the heterogeneity of a space in tension and, from this angle, we can give Mia Couto's style the dialogical feature